Amino acid based poly(ionic liquid) materials for CO2 capture: Effect of anion - Raja Shahrom, M.S. (2019)
Poly(ionic liquid) materials based on eight amino acids (arginine Arg, lysine Lys, histidine Hist, taurine Tau, proline Pro, serine Ser, alanine Ala and glycine Gly) have been synthesized and characterized as CO2 absorbers. Among the broad family studied, Lys was found to have the highest gravimetric uptake with 15.7 wt%. In terms of molar adsorption, the highest CO2 sorption capacity was obtained with VBTMAArg with 0.83 mol/mol and this increased to 1.14 mol/mol after polymerization. The CO2 sorption increased as pressure increased and decreased as temperature was increased. Maximum desorption occurred at 80 Â°C and the materials can be readily recycled with 86% sorption capacity retention demonstrated on the 5th sorption cycle. The molecular-level behavior of the anions was discussed in terms of their activity coefficients and Ï-profiles from COSMO-RS calculations. Â© 2018